Family medicine PreTest self-assessment and review - Knutson, Doug (Douglas J.), 1962- (PreTest self-assessment and review., 2012)
500 USMLE-style questions and answers that address the clerkship's core competencies along with detailed explanations of both correct and incorrect answers. All questions have been reviewed by students who recently passed the boards and completed their clerkship to ensure they match the style and difficulty level of the exam.